P04.11 Profound sensitivity of glioblastoma cells to apoptosis induction by TG02, a novel oral multi-cyclin-dependent kinase inhibitor. (19th September 2018) - Le Rhun, E; von Achenbach, C; Lohmann, B; Silginer, M; Schneider, H; Meetze, K; Szabo, E; Weller, M
Abstract: Background: TG02 is a novel multikinase inhibitor targeting cyclin-dependent kinases (CDK) -1, -2, -5, -7 and -9 and thought to act mainly via CDK-9 inhibition-dependent depletion of short-lived oncoproteins such as MCL-1 or c-MYC. Material and Methods: We studied the activity of TG02 in 9 human long-term glioma cell lines (LTC) and 5 glioma-initiating cell lines (GIC) using various cell death assays in vitro and in the ZH-161 GIC model in vivo . Results: TG02 exhibits strong anti-tumor cell activity with EC50 concentrations in the nanomolar range. Median survival in the ZH-161 model was prolonged by TG02 from 28 to 33 days (p=0.056). Neither constitutive CDK levels nor those of MCL-1 or c-MYC correlated with sensitivity to TG02. Cdk -9 or cdk -5 gene silencing alone did not fully reproduce the effects of TG02. C-myc gene silencing inhibited cell growth, but did not affect TG02 activity. High concentrations of TG02 induced annexin V binding and minor caspase 3 cleavage, and the pan-caspase inhibitor, zVAD-fmk, or BCL-2 or MCL-1 gene transfer moderately attenuated TG02-induced cell death; still, electron microscopy revealed cell death to be essentially apoptotic. TG02 activity was independent of O 6 -methylguanine DNA methyltransferase expression. Repetitive exposure to TG02 did not generate an acquired TG02 resistance phenotype, but accumulation of MCL-1, loss of c-MYC, or senescence. Conclusion: TG02 is a highly potent anti-glioma agent in vitro that appears to induce cell death mainly in an apoptotic, but largely caspase-independent manner. Clinical evaluation of TG02 in glioblastoma is warranted.